Development of Instagram Filters in Interactive E-Books Mathematics Learning Build a Flat Side Space - Annisa Gita Cahyani; Setyadi, Danang (JTMT: Journal Tadris Matematika, 2023)
Abstract In facing the challenges of the 21st century, mathematics must be studied well in the digital world, so that digital learning media can be said to be important in the learning process. This study aims to develop an interactive E-book channeling medium on flat-sided space building materials. The subjects in this study were class VIII students of SMP Negeri 1 Salatiga. This research is Research and Development research. The development model in this study is ADDIE (Analyz, Design, Development, Implementation, and Evaluation). Data collection techniques from this interactive E-book development research are observations, tests, and questionnaires for the assessment of validation, practicality, and effectiveness of interactive E-book media to build a flat side space. The final results of the media validity data analysis are 96.67%, the validity of the material is 86.67%, the practicality is 100%, and the effectiveness of having a significant value of 0.000 or less than 0.05 can be stated that the interactive E-book learning media is "valid, practical and effectively used as a learning medium for students. Abstrak Dalam menghadapi tantangan abad ke-21 matematika harus dipelajari dengan baik diera digital, sehingga media pembelajaran digital dapat dikatakan penting dalam proses pembelajaran. Penelitian ini bertujuan untuk mengembangkan media pembelakaran E-book interaktif pada materi bangun ruang sisi datar. Subjek dalam penelitian ini adalah peserta didik kelas VIII SMP Negeri 1 Salatiga. Penelitian ini adalah penelitian Research and Development atau pengembangan. Model pengembangan dalam penelitian ini ialah ADDIE (Analyz, Design, Development, Implementation, and Evaluation). Teknik pengumpulan data dari penelitian pengembangan E-book interaktif ini adalah observasi, tes, dan angket untuk penilaian validasi, kepraktisan, serta keefektifan media E-book interaktif bangun ruang sisi datar. Hasil akhir analisis data kevalidan media yaitu 96,67%, kevalidan materi yaitu 86,67%, kepraktisan yaitu 100%, dan keefektifan yaitu memiliki nilai signifikan 0,000 atau kurang dari 0,05 dapat dinyatakan bahwa media pembelajara E-book interaktif ” valid, praktis dan efektif digunakan sebagai media pembelajaran peserta didik.